Apparatus to obtain rotational flexibility of the human knee under moment loads in vivo - Mills, O.S.; Hull, M.L. (Journal of biomechanics, 1991)
The contributions of this paper are twofold. One is the design and performance evaluation of new equipment to determine the rotational flexibility of the human knee in vivo. Since determining knee flexibility requires the application of external loads and the measurement of knee rotations, the new equipment consists of a load application stand and a triaxial goniometer. The triaxial goniometer noninvasively mounts to the leg and directly measures the relative three degrees-of-freedom rotations of the knee sequentially and independently. The goniometer incorporates several unique design features which enhance measurement accuracy. The load stand applies pure varus/valgus and external/internal axial moments either individually or in combination through the use of motors controlled by the test subject. Unique to this design are features which enable the application of moments to the knee which minimise shear forces. Other unique design features permit the stand to control hip and knee flexion angles, muscle contraction, and axial loading. To assess the accuracy with which rotations are measured during experiments, three tests were conducted with the equipment. One test evaluated the inherent accuracy of the goniometer, a second test assessed the potential for goniometer slippage during loading, and a third explored the effect of goniometer mounting on the repeatability of results. A special verification apparatus facilitated evaluation of goniometer inherent accuracy. A second contribution of the paper is an investigation of the effect of foot constraints (i.e. boundary conditions) on flexibility results. To make this investigation, three subjects were tested with the knee at 15° of flexion. Results revealed large differences in flexibility between constraining the foot in both external/internal and varus/valgus rotations and permitting the foot to rotate freely in the direction not being loaded. Further, constraint moments as high as 23 Nm were also recorded. These results emphasise that in order to obtain accurate flexibility results for isolated loads, the foot must be unconstrained by the loading apparatus.